Research on Detection and Modification System Based on Virtual Panorama. Issue 3 (April 2019) - Ruan, Jing; Shang, Yanlei
Abstract: In recent years, Web VR has developed rapidly in the wave of VR with its easy accessibility and easy development, and the virtual panorama is particularly prominent. With its comprehensive and vivid display of things, it gradually replaces pictures as display media and information carriers. However, in today's highly competitive environment, it is necessary to improve the stereoscopic and 3D nature of virtual panorama rendering. This paper aims to combine the image detection with the virtual panorama to increase the stereoscopic and 3D nature of the virtual panorama.